"Casados para sempre": um estudo sobre casamento e família segundo a concepção de ambos os cônjuges de casais evangélicos neopentecostais - Ciscon-Evangelista, Mariane Ranzani (2009)
Religious choices may translate into behavioral and conceptual transformations on all levels of the life of the decision maker. A redefinition of aspects of the social identity may result therefrom, as a consequence of the affiliation to a new group. It may also result that interpersonal relationships suffer expressive changes in the way they are lived, specially the relationships with the spouse and children. The objective of this work was to identify, describe and analyze conceptions and practices relative to the interrelated themes of conjugal life, family building, and life project of couples pertaining to a New Pentecostal evangelic group, as well as the comprehension of the implied identitary formation process. Ten couples with active participation in a New Pentecostal church participated on the research. The time elapsed since marriage varied between one and ten years, and not all of the couples had children. Using a semi-structured script, each spouse was interviewed separately, answering about his/her involvement with the religious group, his/her conjugal relationship and relationship with the children, and plans for the future. The data were organized through QSR N6 software and submitted to a content analysis procedure. The results showed that the choice made of a new religious group brought changes on social identity that influenced the interviewees conceptions and practices with respect to people with whom they live, specially towards the spouse and children. The conjugal relationship started to be understood and lived as indissoluble, thus increasing the disposition to administrate the conflicts that appear in the relationship, to forgive, and to renounce to determinate actions and conceptions for the benefit of the relationship. The reports evidenced satisfaction with the religious choice and with the conjugal relationship, few aspects being mentioned with respect to which there is some difficulty. It was found that traditional gender roles are present for the participant couples, in an apparent transformation process for some of them. The decision to have children, or to have more children, was found more influenced by practical and economical aspects, i.e., more on a current priority with respect to the spouses activities, than by the religious involvement.